Some Eastern Orthodox Perspectives on Science-Engaged Theology (and Their Relevance to Western Christians) - Knight, Christopher (Religions, 2024)
An Eastern Orthodox understanding of science—that of Christopher C. Knight—is presented as a contribution to science-engaged theology that has implications for western Christian reflection on science as a contemporary locus theologicus. Three areas of enquiry are discussed: natural theology, the human mind in its relationship to God, and divine action. It is suggested that in each of these areas, Orthodox perspectives can provide links between the differing perspectives to be found among western Christians and provide new pathways for theological exploration on an ecumenical basis.